High-Sensitivity Cardiac Troponin T and Cognitive Function in Patients With Ischemic Stroke. Issue 5 (May 2020) - Broersen, Leonie H.A.; Siegerink, Bob; Sperber, Pia S.; von Rennenberg, Regina; Piper, Sophie K.; Nolte, Christian H.; Heuschmann, Peter U.; Endres, Matthias; Scheitz, Jan F.; Liman, Thomas G.
Abstract : Background and Purpose—: Our study aim was to assess whether high-sensitivity cardiac troponin T (hs-cTnT), a specific biomarker for myocardial injury, is associated with cognitive function in patients after mild-to-moderate first-ever ischemic stroke. Methods—: We used data from PROSCIS-B (Prospective Cohort With Incident Stroke Berlin). Cognitive function was assessed by Mini-Mental-State-Examination at baseline, and Telephone Interview for Cognitive Status–modified after 1 to 3 years of follow-up. Patients were categorized according to hs-cTnT quartiles. We performed generalized linear regression to calculate risk ratios of cognitive impairment (Mini-Mental-State-Examination <27; Telephone Interview for Cognitive Status–modified <32). Association of hs-cTnT with cognitive function over time was estimated using a linear mixed model. Results—: We included 555 patients (mean age, 67 years, 62% male, median National Institutes of Health Stroke Scale 2 [interquartile range, 1–5], hs-cTnT above upper reference limit 40%, baseline cognitive impairment 28%). Baseline Mini-Mental-State-Examination score and rate of cognitive impairment were lower in patients in the highest versus lowest hs-cTnT quartile (median Mini-Mental-State-Examination 27 versus 29, and 15.3% versus 43.0%, adjusted risk ratio, 1.76 [95% CI, 1.07–2.90], respectively). If anything, cognition seemed to improve in all groups, yet Telephone Interview for Cognitive Status–modified scores were consistently lower in patients within the highest versus lowest hs-cTnT quartile (adjusted β, −1.33 [95% CI, −2.65 to −0.02]), without difference in the rate of change over time. Conclusions—: In patients with mild-to-moderate first-ever ischemic stroke without dementia, higher hs-cTnT was associated with higher prevalence of cognitive impairment at baseline and lower Telephone Interview for Cognitive Status–modified during 3-year follow-up. Registration—: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01363856. Abstract : Supplemental Digital Content is available in the text.